2020
DOI: 10.3389/fonc.2020.577636
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of SRSF3 as a Therapeutic Target for Cancer

Abstract: Ser/Arg-rich (SR) proteins are RNA-binding proteins known as constitutive and alternative splicing (AS) regulators that regulate multiple aspects of the gene expression program. Ser/Arg-rich splicing factor 3 (SRSF3) is the smallest member of the SR protein family, and its level is controlled by multiple factors and involves complex mechanisms in eukaryote cells, whereas the aberrant expression of SRSF3 is associated with many human diseases, including cancer. Here, we review state-of-the-art research on SRSF3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 166 publications
(279 reference statements)
2
30
0
Order By: Relevance
“…In addition, several RBP motifs in both the 5ʹ‐ and 3ʹ‐UTR were predicted to be affected: c.‐68T>C disrupted a potential SRSF3 motif and created an RBM6 motif; c.*529A>G disrupted predicted motifs for HNRNPL, IGF2BP2, RBM41, and SRSF3 RNA binding factors and generated a new sequence expected to bind SRSF5 (Table S2 ). These RNA‐binding proteins (or their closely related family members) have demonstrated important roles in RNA‐regulation (including splicing, export, stability, polyadenylation, and translation) (Cao et al, 2018 ; Jain et al, 2012 ; Oberdoerffer et al, 2008 ; Rothrock et al, 2005 ; Sutherland et al, 2005 ; Twyffels et al, 2011 ; Zhong et al, 2009 ; Zhou et al, 2020 ); in addition, SRSF3 and HNRNPL showed associations with ocular disease, mainly glaucoma (Jain et al, 2012 ; Schmitt et al, 2020 ). Finally, in silico evaluations using FATHMM‐MKL predicted deleterious effects, and GERP++RS and PhyloP indicated nucleotide conservation for both 5ʹ‐ and 3ʹ‐UTRs (Table 1 and Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several RBP motifs in both the 5ʹ‐ and 3ʹ‐UTR were predicted to be affected: c.‐68T>C disrupted a potential SRSF3 motif and created an RBM6 motif; c.*529A>G disrupted predicted motifs for HNRNPL, IGF2BP2, RBM41, and SRSF3 RNA binding factors and generated a new sequence expected to bind SRSF5 (Table S2 ). These RNA‐binding proteins (or their closely related family members) have demonstrated important roles in RNA‐regulation (including splicing, export, stability, polyadenylation, and translation) (Cao et al, 2018 ; Jain et al, 2012 ; Oberdoerffer et al, 2008 ; Rothrock et al, 2005 ; Sutherland et al, 2005 ; Twyffels et al, 2011 ; Zhong et al, 2009 ; Zhou et al, 2020 ); in addition, SRSF3 and HNRNPL showed associations with ocular disease, mainly glaucoma (Jain et al, 2012 ; Schmitt et al, 2020 ). Finally, in silico evaluations using FATHMM‐MKL predicted deleterious effects, and GERP++RS and PhyloP indicated nucleotide conservation for both 5ʹ‐ and 3ʹ‐UTRs (Table 1 and Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…SRSF3 is an SR family protein that possesses an N-terminal RNA-binding RNA recognition motif (RRM) and a C-terminal arginine/serine (RS)-rich domain responsible for protein-protein and protein-RNA interactions. SRSF3 is a multifunctional splicing factor involved in transcriptional, co-transcriptional, and post-transcriptional regulation and has been implicated in a variety of human pathologies including heart disease, Alzheimer’s, and cancer (More & Kumar, 2020; Zhou et al, 2020). Examination of our paired RNA-seq and Ribo-seq data revealed robust expression of SRSF3 NMD-targeted exon 4 after 8 h of DUX4 induction, followed by robust translation of this exon that ends at the site of the PTC ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…After computational analysis, we identified eleven miR-21-5p-related genes that encode proteins that interact with various BOS-related genes. Some of these reported targets are cancer-related and are associated with carcinogenesis (such as SPRY2, SKY and SRSF3), cancer prognosis (such as CNOT6, RECK and GID4) or cancer cell plasticity (such as RMND5A) [ 28 , 29 , 30 , 31 ]. Interestingly, between these targets only STAT3 and PCBP1 showed more interactors.…”
Section: Discussionmentioning
confidence: 99%